Shifts in the pelagic ammonia-oxidizing microbial communities along the eutrophic estuary of Yong River in Ningbo City, China - Zhang, Qiufang; Tang, Fangyuan; Zhou, Yangjing; Xu, Jirong; Chen, Heping; Wang, Mingkuang; Laanbroek, Hendrikus J. (Frontiers in Microbiology, 2015)
Aerobic ammonia oxidation plays a key role in the nitrogen cycle, and the responsible microorganisms diversities are regulated by environmental factors. Abundance and composition of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) were investigated in the surface waters along an environmental gradient of Yong River in Ningbo, China. Water samples were collected from three zones: freshwaters in urban canals, brackish waters in the downstream Yong River, and coastal water of Hangzhou Bay. Shifts in activity and diversity of the ammonia oxidizers occurred with changes in salinity, ammonium and oxygen. The AOA abundance was always higher than that of AOB and related to the ammonia oxidation activity. The ratios of AOA/AOB in the brackish and marine waters were significantly higher than those found in freshwaters. Both AOA and AOB showed similar community compositions in brackish and marine waters, but only 31 and 35% similarity, respectively, between these waters and the urban inland freshwaters. Most of AOA-amoA sequences from freshwater were affiliated with sequences obtained from terrestrial environments and those collected from brackish and coastal areas were ubiquitous in marine, coastal, and terrestrial ecosystems. All AOB from freshwaters belonged to Nitrosomonas, and those from brackish and marine waters mainly belonged to Nitrosospira.